Acute Lesion Imaging in Predicting Chronic Tissue Injury in the Ventricles - El Hajjar, Abdel Hadi; Huang, Chao; Zhang, Yichi; Mekhael, Mario; Noujaim, Charbel; Dagher, Lilas; Nedunchezhian, Saihariharan; Pottle, Christopher; Kholmovski, Eugene; Ayoub, Tarek; Dhorepatil, Aneesh; Barakat, Michel; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Chronic lesion formation after cardiac tissue ablation is an important indicator for procedural outcome. Moreover, there is a lack of standardization for ablation parameters that predict chronic lesion formation. Objective: The aim of this study is to determine whether acute lesion visualization using late gadolinium enhanced magnetic resonance imaging (LGE-MRI) can reliably predict chronic lesion size. Methods: Fifty-Five ventricular lesions were induced in canine models using either radiofrequency (RF) ablation or cryofocal ablation. Multiple ablation parameters were used. The first LGE-MRI was captured within the first hour post-ablation and the second LGE-MRI was obtained 47 to 82 days later. Corview software was used to perform lesion segmentations and size calculations. Results: Fifty-Five lesions were created in different locations in the ventricles. Lesion volume reduction demonstrated a linear trend. Chronic volume size decreased by a mean of 62.5 % (95% CI 58.83-67.97, p-value <0.0005). This trend is observed regardless of ablation location (p=0.32), ablation technique (p=0.94), duration (p=0.37), power (p=0.55) and whether lesions were connected or not (p=0.35). There was no significant difference in lesion volume reduction assessed at 47-54 days and 72-82 days after ablation (p=0.31). Chronic lesion volume was equal to 0.32 of the acute lesion volumes (R2=0.75). Conclusion: Chronic tissue injury related to catheter ablation can be reliably modeled as a linear function of the acute lesion volume as assessed by LGE-MRI, regardless of the ablation parameters.